Contribution of PCA/K-means methods to the mixed assessment of patient safety culture - Fourar, Youcef-Oussama; Djebabra, Mébarek; Benhassine, Wissal; Boubaker, Leila (International Journal of Health Governance, 2021)
Purpose The assessment of patient safety culture (PSC) is a major priority for healthcare providers. It is often realized using quantitative approaches (questionnaires) separately from qualitative ones (patient safety culture maturity model (PSCMM)). These approaches suffer from certain major limits. Therefore, the aim of the present study is to overcome these limits and to propose a novel approach to PSC assessment. Design/methodology/approach The proposed approach consists of evaluating PSC in a set of healthcare establishments (HEs) using the HSOPSC questionnaire. After that, principal component analysis (PCA) and K-means algorithm were applied on PSC dimensional scores in order to aggregate them into macro dimensions. The latter were used to overcome the limits of PSC dimensional assessment and to propose a quantitative PSCMM. Findings PSC dimensions are grouped into three macro dimensions. Their capitalization permits their association with safety actors related to PSC promotion. Consequently, a quantitative PSC maturity matrix was proposed. Problematic PSC dimensions for the studied HEs are “Non-punitive response to error”, “Staffing”, “Communication openness”. Their PSC maturity level was found underdeveloped due to a managerial style that favors a “blame culture”. Originality/value A combined quali-quantitative assessment framework for PSC was proposed in the present study as recommended by a number of researchers but, to the best of our knowledge, few or no studies were devoted to it. The results can be projected for improvement and accreditation purposes, where different PSC stakeholders can be implicated as suggested by international standards.